Puzzle Play and Fine Motor Development among Children Aged 4–5 Years - Nurrahmaton; Nuriah Arma; Sumita Sitompul (PT Bukuloka Literasi Bangsa, 2026)
Introduction: Preschool age is a critical period for child development, including fine motor skills. However, fine motor developmental delays are still found among preschool children. Puzzle play is considered one of the educational activities that may help stimulate fine motor development. Initial observations at YPP Generasi Bangsa Tangkahan Kindergarten, Medan Labuhan, showed that several children experienced difficulties in activities such as folding, drawing, and imitating writing. Objective: This study aimed to determine the relationship between puzzle play and fine motor development among children aged 4–5 years at YPP Tangkahan Nation Generation Kindergarten, Medan Labuhan, in 2025. Method: This study used a descriptive correlational design with a cross-sectional approach conducted at YPP Generasi Bangsa Tangkahan Kindergarten, Medan Labuhan, in 2025. The respondents were 33 children aged 4–5 years who met the inclusion criteria and were selected using a total sampling technique. Data were collected through direct observation using the Denver Developmental Screening Test II (DDST II) instrument. Fine motor assessment for children aged 4–5 years included activities such as drawing shapes, folding paper, arranging objects, and imitating writing according to the DDST II guidelines. Data were analyzed using the Chi-Square test. Results: The results showed that 22 children (66.7%) were categorized as having normal fine motor development, while 11 children (33.3%) were categorized as suspect. Based on column percentages in the crosstab analysis, among children with appropriate puzzle-play activities, 20 children (83.3%) had normal fine motor development and 4 children (16.7%) were categorized as suspect. Meanwhile, among children with inappropriate puzzle-play activities, 2 children (22.2%) had normal fine motor development and 7 children (77.8%) were categorized as suspect. Statistical analysis using Fisher’s Exact Test showed a significant relationship between puzzle play and fine motor development among children aged 4–5 years at YPP Generasi Bangsa Tangkahan Kindergarten, Medan Labuhan, in 2025 (p < 0.001). Conclusion: Puzzle play was associated with fine motor development among children aged 4–5 years. Puzzle activities may be used as a practical form of stimulation to support children’s fine motor skills development at home and in educational settings. Further studies with larger samples and different research designs are recommended to strengthen the findings. Keywords: Puzzle play; Fine motor development; Preschool children; Educational games; Child development.